2022
DOI: 10.1007/s00253-022-11860-y
|View full text |Cite
|
Sign up to set email alerts
|

Highly mercury-resistant strains from different Colombian Amazon ecosystems affected by artisanal gold mining activities

Abstract: Two sites of the Colombian Amazon region with different levels of human intervention and mercury pollution were selected for the collection of samples of river and lake water, sediments, and associated forest soils. The Tarapacá region, affected mainly by barrage mining, showed low mercury concentrations, whilst in the Taraira region, affected by underground mining, there were several points with high mercury pollution levels. A collection of 72 bacterial and 10 yeast strains with different levels of mercury r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Several related studies have shown that bacteria from Pseudomonas and Staphylococcus groups were also found to be MRB, as observed in the studies by [32,33]. Furthermore, various studies have been conducted regarding the application of Pseudomonas and Staphylococcus MRB as bioremediation agents, demonstrating their potential in reducing mercury contamination in environments [34].…”
Section: Discussionmentioning
confidence: 93%
“…Several related studies have shown that bacteria from Pseudomonas and Staphylococcus groups were also found to be MRB, as observed in the studies by [32,33]. Furthermore, various studies have been conducted regarding the application of Pseudomonas and Staphylococcus MRB as bioremediation agents, demonstrating their potential in reducing mercury contamination in environments [34].…”
Section: Discussionmentioning
confidence: 93%
“…It was negative for oil hydrolysis, VP, and H 2 S. The phylogenetic tree of the strain is shown in Figure 1 d, and the 16S rDNA gene sequence comparison showed that the strain was 99% similar to strain LBA119 and strain KT758473.1 Bacillus aryabhattai. The strain LBA119 was identified as Bacillus [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extensive findings regarding HRGs in this study enrichened the gene sources for the exploitation of the mer-mediated functions for the Hg bioremediation [ 44 ]. Along with the fairly high diversity of HRG clusters, the transcription of HRGs can be activated in diverse ways, e.g., the merA transcription activation in Thermus thermophilus [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have reported finding the HRG and ARG co-distribution in various complex environments or in single microorganisms [ 20 , 21 , 24 , 45 , 46 ]. We found that there were 1368 plasmids harboring both HRGs and ARGs, representing approximately 7.30%, 79.40%, and 22.13% of all analyzed plasmids, plasmids with HRGs, and plasmids with ARGs, respectively ( Table S4 ).…”
Section: Resultsmentioning
confidence: 99%